How does the geographic export diversification–performance relationship vary at different levels of export intensity?. Issue 6 (December 2016) - Boehe, Dirk Michael; Jiménez, Alfredo
Highlights: The export diversification–performance relationship depends on export intensity. The relationship is S-shaped if export intensity is low. The relationship is inverted U-shaped if export intensity is high. Commitment to export markets changes the cost-benefit of export diversification. Our analysis of large Brazil exporters from 2001 to 2010 supports our hypotheses. Abstract: We argue that the relationship between geographic export diversification and firm performance follows an S-curve relationship if export intensity is low and an inverted U-shape if export intensity is high. The S-shape curve occurs because firms have weaker incentives to deploy the resources needed for succeeding in foreign markets if they generate relatively low revenues in export markets compared to their domestic market. Firms highly committed to export markets, in contrast, face stronger incentives to accelerate their learning curve, which results in an inverted U-shape relationship. We examine our hypotheses using a panel of longitudinal archival data with over 2000 firm-year observations, which cover all of the possible export destination countries served by large Brazil-based exporters from 2001 to 2010. Our results imply that the degree of export intensity changes the cost-benefit relationship of geographic export diversification.